Childhood maltreatment, serotonin transporter gene, and risk for callous and unemotional traits: A prospective investigation. (September 2020) - Widom, Cathy Spatz; Miller, Dana; Li, Xuechen; Gordon, Derek; Brzustowicz, Linda
Highlights: Although associations have been reported between the serotonin transporter 5-HTTLPR genotype and antisocial and aggressive traits and between child maltreatment and antisocial traits, few studies have examined whether 5-HTTLPR moderates the influence of childhood maltreatment on these traits. This unique investigation uses data from a prospective longitudinal design study, documented cases of childhood maltreatment, a demographically matched control group, and assessment of callous-unemotional traits in adulthood. Childhood maltreatment predicted higher callous-unemotional traits scores in adulthood, but the effect of child maltreatment on callous-unemotional trait scores did not differ by genetic risk. In contrast, matched controls (non-maltreated) with the LL (high activity) genotype had higher callous-unemotional trait scores. Having a history of childhood maltreatment or the LL genotype (associated with higher risk) predicted higher levels of callous and unemotional trait scores in adulthood. Abstract: Previous studies have reported associations between the serotonin transporter 5-HTTLPR genotype and antisocial and aggressive traits and between child maltreatment and antisocial traits. However, few studies have examined whether 5-HTTLPR moderates the influence of childhood maltreatment on callous and unemotional traits, a hallmark of psychopathy. Using a prospective cohort design, children with documented cases of maltreatment and matched controls were followed up and interviewed in adulthood. DNA was extracted from blood and saliva ( N = 414) and callous-unemotional (CU) traits were assessed. Childhood maltreatment predicted higher CU scores in adulthood, whereas the effect of 5-HTTLPR was not significant. The effect of child maltreatment on CU traits did not differ by genetic risk (high or low activity 5-HTTLPR), whereas controls with the LL genotype had higher CU scores than controls with the SS genotype. Similar results were found for females and White, non-Hispanics, but not for males and Blacks. Variations in 5-HTTLPR did not affect the impact of child maltreatment on CU traits in adulthood. Genetic risk had a stronger effect on adults with lower environmental risk (controls). Having a history of child maltreatment or the LL genotype placed participants at risk for higher levels of callous and unemotional trait scores.